Social Capital: Strategy of Takmir of Jogokariyan Mosque on Developing the Worshipers - Hidayat, Wahyu Panca (UIN Sunan Gunung Djati Bandung, 2015)
This paper discusses a phenomenon of mosqueâs worshipers as a social capital. Jogokariyan Mosque is, named after the village, located in Special District of Yogyakarta, Indonesia, and has a dynamic worshipers based on its activities. Dynamic because its activities could establish trustworthiness among them. Historically, existence of Muhammadiyah, as an Islamic dakwah body, since 1960s constructs norms that refer to Islamic values. The length of existence of Muhammadiyah movement builds unique networking among the alumni of Takmir of Jogokariyan Mosque which then is used to support mosqueâs movements. Thus, social capital analysis based on Robert D. Putnamâs perspective, which contains norms, networks, and trust is relevant to draw social capital phenomenon in Jogokariyan village with mosque as the key of this movement.